Perancangan Layanan Elektronik Informasi Komersial Terpadu Kota Makassar - Elisabeth; Anugrah Christian Pratama Kamisi; Adi Chandra Syarif (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2015)
One of the challenges faced by in managing information in a city is how to structure the various kind of data in many different forms to be easily access and shared among the coummunity. One important aspect of public service for a city is the accessibility of information. This research focuses on the design of a structured method which has several stages of analysis to solve the problem of the need for information about the city of Makassar. The results of this study to help the community in order to more easily obtain information about the datails of Makassar city, and provide the opportunity for the agencies working together to promote their businesss.